Diverse Role of TGF-β in Kidney Disease - Gu, Yue-Yu; Liu, Xu-Sheng; Huang, Xiao-Ru; Yu, Xue-Qing; Lan, Hui-Yao (Frontiers in Cell and Developmental Biology, 2020)
Inflammation and fibrosis are two key pathological features of chronic kidney disease (CKD). Excessive renal inflammation leads to progressive renal fibrosis, which eventually results in the end-stage renal disease (ESRD). Transforming growth factor-β (TGF-β) has been considered as a master regulator that diversely regulates inflammation and fibrosis via both canonical and non-canonical signaling pathways. In the context of renal fibrosis, TGF-β1 is pathogenic. In contrast, TGF-β is also a potent anti-inflammatory cytokine that functions to regulate immune response on both immune cells and intrinsic kidney cells. Thus, generally blocking TGF-β signaling inhibits renal fibrosis but promotes renal inflammation. Mechanistically, TGF-β1 may activate its downstream signaling molecule Smad3 to transcriptionally and differentially regulate renal inflammation and fibrosis via Smad3-dependent non-coding RNAs, including miRNAs and l¬¬ncRNAs, which are negatively regulated by Smad7. All these findings underly the complexity of TGF-β1 in renal inflammation and fibrosis. Thus, treatment of renal fibrosis and inflammation by specifically targeting Smad3 and Smad3-dependent non-coding RNAs or by overexpressing Smad7 have been developed. In this review, the paradoxical functions and underlying mechanisms of TGF-β1 in diversely regulating renal inflammation and fibrosis are discussed and novel therapeutic strategies for kidney disease by targeting downstream TGF-β/Smad signaling and transcriptomes are highlighted.